A Qualitative Study on the Tax Amnesty Perception of Income Taxpayers: The Case of Türkiye - Serap Püren (International Journal of Public Finance)
Tax amnesty, which is not regulated in the Tax Procedure Law, has been implemented from time to time since 1924. Tax amnesty, which is seen as an urgent source of income for governments, can have positive or negative consequences for taxpayers. It is understood from the literature that the opinions on tax amnesty practices are divided into two as positive and negative and that there is no full consensus on the subject. The study aims to concretize the theory with a qualitative analysis of the participant opinions covering five different types of taxpayers subject to income tax. For this purpose, content analysis was used in the qualitative study and for this analysis, semi-structured interviews were conducted with five groups of taxpayers subject to income tax (commercial, agricultural, self-employment income, real estate capital income, wage earners) and the results were analyzed with the QSR Nvivo program. Although the analysis results do not present surprising results, they concretely reveal the opinions of income taxpayers on tax amnesty through direct quotations. The results showed that tax amnesties frequently implemented by governments cause taxpayers to expect a new amnesty and cause tax compliance to deteriorate, and are perceived as unfair and unjust by taxpayers who fulfill their tax obligations. In this sense, it was revealed from the qualitative analysis results that taxpayer opinions support the negative view in the theory and literature on tax amnesty practices, but they may accept tax amnesty to revive the economy during or after economic, political or financial crises. In addition to contributing to the literature by focusing on taxpayer opinions in order to concretize the views in the theory and literature on tax amnesty, the qualitative study also draws attention to the need for tax policies to be implemented for a more equitable application of tax amnesties perceived as unjust and offers suggestions.